FEATURES OF PAIN SYNDROME IN PATIENTS WITH MULTIPLE SCLEROSIS - Maksymchuk, L. T.; Gryb, V. A.; Doroshenko, O. O.; Genyk, S. I.; Gerasymchuk, V. R.; Sorokhman, A. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The data of 61 medical cards of patients with multiple sclerosis has been analyzed. 47,54% of patients reported pain as a symptom of multiple sclerosis, following types of pain were observed: neuropathic pain (оngoing extremity pain, Lhermitte's phenomenon), nociceptive pain (headache, back pain) and mixed pain (painful tonic spasms, spasticity pain). Only 17,24% of patients received therapy to treat pain.